Young People's mental health service utilization - Driessens, Corine; Smith, Peter W.F.; Markham-Jones, Kim; Lacey, Fiona (International Journal of Population Data Science, 2025)
Objective This project aimed to uncover key factors that shape young people’s (YP) mental health care utilization. The Andersen’s Behavioral Model of Health Care Utilization was adapted in co-production, providing a framework for the predisposing characteristics, enabling resources, and perceived/evaluated need factors hypothesized to influence young people’s mental health care utilization. Methods The project is a secondary data analysis project with strong emphasis on YP involvement. YoungMinds and young researchers facilitated the co-production of an analysis plan with YP who had lived experience. This analysis plan was used to analyse existing data (Longitudinal Study of YP in England, also known as NEXT STEPS). Cohort data was linked to administrative health care data (Hospital Episode Statistics) to obtain objective measures of mental health care utilization. As this cohort is subjective to mental health related attrition, logistic regression models in combination with missing-not-at-random methodology was used to determine factors impacting mental health service utilization. Results The insights and experiences shared by YP in three workshops were captured in the YP’s model of secondary health care utilization for common mental health problems. NEXT STEPS-HES linked data showed that approximately 10% of the participants reporting common mental health problems between age 14 to 25 accessed secondary mental health services. The main predictor of utilization of secondary mental health services between age 17 to 25 is having a common mental health diagnosis before age 17. Interaction with social services and educational welfare at age 16 also facilitates utilization of mental health care services. Findings align with existing literature showing that women are more likely to utilize secondary mental health care services compared to men. Conclusion Despite growing recognition of mental health challenges among young people (YP), the findings indicate that only one in ten YP reporting common mental health problems utilized services. Secondary mental health care use was not only influenced by perceived mental wellbeing but also by societal perceptions and expectations.